Combination of private law and public law principles in the regulation of investment relations - Hnativ, Oksana; Rym, Taras; Tsikalo, Volodymyr; Rym, Olena (P.A. Persona e Amministrazione, 2023)
Regulatory documents aimed at governing relations contain both private law and public law norms. There are not so many monoimperative legal acts in the legislation of Ukraine, and there are no monodispositive ones whatsoever. Only the right combination of dispositive and imperative prescriptions will allow achieving the desired result of legal regulation. This ensures a balance of interests of all participants in the investment process. An equally important aspect of the legal regulation of investment activity is the attraction of foreign investment, which is necessary to ensure sustainable economic development. However, creating a favourable investment climate for foreign investors cannot discriminate against the national commodity producer. State participation in international organisations and international treaties has an undeniable impact on ensuring the balance of private and public interests in these circumstances. It was established that efficient legal regulation of investment activities requires a combination of private law and public law foundations (principles), which will ensure proper conditions for investment activities. Private law principles ensure equal rights for all participants in investment relations, recognise the value of the investor's rights, and provide an opportunity to choose objects, forms, and spheres of investment activity. Thus, investment relations undergo a dispositive impact.